El Excentrico, 1969-09-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
September 5, 1969 [5 de septiembre de 1969]. No volume or issue number. Cover has a photograph of model America Martin, along with a smaller photograph of Hank Coca. The headline reads, "America Martin to appear in person at Hank Coca's Furniture Discount House." She made here appearance at the Furniture Discount House on September 6 and 7 at noon.